Kemalasan sosial, persepsi dukungan organisasi, komitmen organisasi, kepuasan kerja - Azwar Azwar; Nofrans Eka Saputra; Iin Indrawati (Fakultas Kedokteran dan Ilmu Kesehatan Universitas Jambi, 2017)
INTRODUCTION Job satisfaction became an issue that tends to disputed for employees who works within the family company which has a certain ethnic background, ie Minang. Job satisfaction’s indicator can be predicted by social loafing, perceived organizational support, and organizational commitment because they have the same ethnic. This study aims to prove the relationship between social loafing, perceived organizational support, and organizational commitment with job satisfaction of employees of the company family. METHOD This study used cross sectional approach. The research population is all employee who is registered as a family company of Minang ethnic employees (X), have minimum worked more than 3 months, not hired as temporary employee/civil servant, ethnic: Minang, Malay, Java, and Batak. Sampling technique using total sampling as many as 73 employees. Collecting data use job satisfaction scale, social loafing scale, perceived organizational support scale, and organizational commitment scale. Data analysis method using regression analysis. RESULT This study shows there was a significant relation between social loafing, organizational commitment, perceived organizational support with the job satisfaction on the family company’s employee (54 %) with F score 29,204. Social loafing has negative relation that so significant with the job satisfaction (18,8 %). Perceived organizational support has positive relation that so significant with job satisfaction (38,8 %). Organizational commitment has significant relation with job satisfaction (13,3 %). Perceived organizational support has significant relation with organizational commitment (21,9 %). CONCLUSSIONS AND RECOMENDATIONS Job satisfaction of employees who working in the family company are predictable by social loafing, perceived organizational support, and organizational commitment even though the employees have a different ethnic backgrounds with the owner. Keywords : Job Satisfaction, Social loafing, Perceived Organizational Support, Organizational